The worship of Love - Mohamed, Ferial (Department of English Language and Literature, 2021)
Rania, a young introverted woman, lives in a traditional Muslim family. It is a working class family, of Indian and Cape Malay heritage. Her parents married each other against her paternal grandmother's plans for her son, and because of their disapproval of Rania's mother, it caused a rift isolating both Rania and her mother from them. Rania feels stuck in an environment where she doesn't fit in and feels that she doesn't belong. Feeling like this, she escapes into a dream world of books and art to survive her overbearing mother, Shazia, who is both emotionally repressed and verbally abusive toward her. Her father, Ismail (Miley) Ahmed, fuels the drama with his obsessive control which Rania questions, yet obeys. Shazia, heartbroken from a previous love lost, pretends not to be interested in the silliness of love, and feigns disinterest in her husband's suspected extramarital affairs, yet does everything she can to hold onto him. Until he humiliates her beyond her capacity to forgive and she throws him out, but still secretly holds onto a hope that he will want to come back to her. Amara is Shazia's daughter from her previous husband, Rania's stepsister, and Shazia's favourite. Shazia has great plans for her, but she is a strong and free spirited young woman, and rebels against her doting mother by following her own bliss. She chooses happiness over security, even if it means defying her mother's wishes and breaking her mother's heart. Rania, obedient and lonely, yearns to meet someone she can connect to, someone who can save her from the world she believes her parents are keeping her trapped in, but she may be the one blocking herself. It is a coming of age story where three women struggle to find happiness amid difficult circumstances. The events which unfold, change their lives forever.